Depression in heart failure: Intricate relationship, pathophysiology and most updated evidence of interventions from recent clinical studies. (1st December 2016) - Ghosh, Raktim K; Ball, Somedeb; Prasad, Vinita; Gupta, Anjan
Abstract: Heart failure (HF) is a burgeoning chronic health condition affecting more than 20 million people worldwide. Patients with HF have a significant (17.1%) 30-day readmission rate, which invites substantial penalty in payment to hospitals from Centers for Medicare and Medicaid Services, as per the newly introduced Hospital Readmissions Reduction Program. Depression is one of the important risk factors for readmission in HF patients. It has a significant prevalence in patients with HF and contributes to the overall poor quality of life in them. Several behavioral (smoking, obesity, lack of exercise and medication noncompliance) and pathophysiological factors (hypercortisolism, elevated inflammatory biomarkers, fibrinogen, and atherosclerosis) have been found responsible for the adverse outcome in patients with HF and concomitant depression. Hippocampal volume loss noted in patients with acute HF exacerbations may contribute to the development of depressive symptoms in them. Screening for depression in HF patients continues to be challenging due to a considerable overlap in symptoms. Published trials on the use of antidepressants and cognitive behavioral therapy (CBT) have shown variable outcomes. Newer modalities like internet-based CBT have been tried in small studies, with promising results. A recent meta-analysis observed the beneficial role of aerobic exercise training in patients with HFrEF. Future long-term prospective studies may contribute to the formulation of a detailed screening and management guideline for patients with HF and depression. Our review is aimed to summarize the intricate relationship between depression and heart failure, with respect to their epidemiology, pathophysiological aspects, and optimal management approach. Highlights: Depression is an important risk factor for heart failure (HF)-related readmissions. Diagnosis often challenging due to overlapping symptoms. Intricate interplay of neuroendocrine system and inflammatory biomarkers. Use of antidepressants leads to variable outcomes in HF. Aerobic exercise and internet-based CBT showed promising results.